Ethnomedicinal survey of some plants used for the treatment of diabetes in Ibadan, Nigeria - Ofuegbe, OS; Adedapo, AA (Asian Journal of Medical Sciences, 2015)
Objectives: A comprehensive survey with the aim of documenting traditional medicinal practices was carried out in targeted areas of Ibadan, Nigeria in order to inventory plants used by traditional healers in the area for the management of diabetes. Materials and Methods: Open-ended informal interviews were administered during series of repeated visits to the respondents consisting majorly the traditional medical practitioners (TMPs) and herb sellers. Some traditional healers who know and use medicinal plants for treating diabetes mellitus were interviewed. The inventory contains scientifi c, vernacular, common names of the plants used and methods of preparation. Results: Twenty seven plants commonly used by traditional healers in the region were identifi ed. These plants were found to be very important and useful in the treatment of diabetes based on their frequency of occurrence in the recipes obtained. Herbal remedies were either prepared from dried or freshly collected plants while traditional solvent of choice included water, lime, local gin and aqueous extract from fermented maize. Decoction and pulverization were the main methods of preparation while mode of administration varies within 1 to 3 times daily. Survey revealed that leaves form the major part of plants for herbal preparations. Residents in the study area fi nd traditional medicine cheaper as compared to orthodox medicine. Conclusion: This review focuses on the various plants that have been reported to be effective in the treatment of diabetes. The survey shows that plants from the Rubiaceae, Labiataceae, Meliaceae, Hypoxidaceae and Cucurbitaceae families are commonly used by traditional healers in Ibadan for the treatment of diabetes mellitus. DOI: http://dx.doi.org/10.3126/ajms.v6i5.10480 Asian Journal of Medical Sciences Vol.6(5) 2015 36-40